New topological invariants for real- and angle-valued maps : an alternative to Morse-Novikov theory - Burghelea, Dan (Singapore : World Scientific, 2018)
This book presents an alternative to what the topologists refer to as "Morse-Novikov theory", a mathematical theory which belongs to the fields of geometry and topology.
Includes bibliographical references and index.
Keywords: Manifolds (Mathematics); Mappings (Mathematics); Topological spaces